2020
DOI: 10.1093/molbev/msaa117
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Epidemiology, Evolution, and Transmission Dynamics of Porcine Deltacoronavirus

Abstract: Abstract The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has shown once again that coronavirus (CoV) in animals are potential sources for epidemics in humans. Porcine deltacoronavirus (PDCoV) is an emerging enteropathogen of swine with a worldwide distribution. Here, we implemented and described an approach to analyze the epidemiology of PDCoV following its emergence in the pig population. We performed an integrated analysis of full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
114
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(119 citation statements)
references
References 84 publications
3
114
2
Order By: Relevance
“…Recent serological data confirm the presence of swine PDCoV IgG antibodies as early as 2010 ( 32 ). The fact that the diversity of PDCoV in US swine is restricted (≥99.7% nucleotide identity) ( 31 , 33 , 34 ) is also consistent with the relatively recent introduction of the virus. While the exact route of emergence of PDCoV in the US is unknown, Asia is considered to be the area of PDCoV origin, where no association of this pathogen with significant clinical disease was reported ( 28 ).…”
Section: Porcine Deltacoronavirusmentioning
confidence: 55%
See 1 more Smart Citation
“…Recent serological data confirm the presence of swine PDCoV IgG antibodies as early as 2010 ( 32 ). The fact that the diversity of PDCoV in US swine is restricted (≥99.7% nucleotide identity) ( 31 , 33 , 34 ) is also consistent with the relatively recent introduction of the virus. While the exact route of emergence of PDCoV in the US is unknown, Asia is considered to be the area of PDCoV origin, where no association of this pathogen with significant clinical disease was reported ( 28 ).…”
Section: Porcine Deltacoronavirusmentioning
confidence: 55%
“…He et al have recently demonstrated the presence of at least four distinct phylogenetic lineages of PDCoV that differ in their geographic circulation patterns ( 34 ). Of interest, more frequent intra- and inter-lineage recombination events (resulting in higher virus genetic diversity) were observed among PDCoV strains of the Chinese lineage than among those of the US lineage.…”
Section: Porcine Deltacoronavirusmentioning
confidence: 99%
“…This suggests possible periodic outbreaks of SADS-CoV could be observed in years to come. PDCoV, a δ-coronavirus, was first detected in 2012 and caused PEDV-like signs in pigs [19][20][21]22]. Birds can be considered as the natural hosts of δ-coronaviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus S protein is a granule-shaped structural protein with a length of about 1200 aa, which helps the virus to bind to cell receptors and participate in mediating viral infection and pathogenesis [11,12]. During viral infection, the host cell PCs cleave the S1/S2 cleavage site of the trimer S protein dividing it into an N-terminal S1 extracellular domain that recognizes the relevant cell surface receptor and a C terminal S2 membrane anchor protein that is involved in translocation of the virus into the cells [13,14]. SARS-Cov-S2 and SARS-CoV-S1 proteins contain a conserved receptor-binding domain (RBD), which can recognize ACE2 [15].…”
Section: Introductionmentioning
confidence: 99%